2016
DOI: 10.1089/trgh.2015.0008
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Effects of Hormone Therapy on Psychological Functioning and Quality of Life in Transgender Individuals

Abstract: ObjectivesTo review evidence from prospective cohort studies of the relationship between hormone therapy and changes in psychological functioning and quality of life in transgender individuals accessing hormone therapy over time.Data SourcesMEDLINE, PsycINFO, and PubMed were searched for relevant studies from inception to November 2014. Reference lists of included studies were hand searched.ResultsThree uncontrolled prospective cohort studies, enrolling 247 transgender adults (180 male-to-female [MTF], 67 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
197
2
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 321 publications
(215 citation statements)
references
References 17 publications
4
197
2
12
Order By: Relevance
“…However, surprisingly in the full sample, those who had medically transitioned were more likely to report self-harm. This is inconsistent with previous research, which has indicated the positive benefits of medically transitioning to mental health (White Hughto & Reisner, 2016). Although medical transition is important for bringing one’s body in line with one’s gender identity, it is possible that the stigma that persists after medical transition, particularly for those with high visual gender nonconformity (i.e., those who are not recognized as their affirmed gender), negatively affects health in the form of self-harm.…”
Section: Discussioncontrasting
confidence: 99%
“…However, surprisingly in the full sample, those who had medically transitioned were more likely to report self-harm. This is inconsistent with previous research, which has indicated the positive benefits of medically transitioning to mental health (White Hughto & Reisner, 2016). Although medical transition is important for bringing one’s body in line with one’s gender identity, it is possible that the stigma that persists after medical transition, particularly for those with high visual gender nonconformity (i.e., those who are not recognized as their affirmed gender), negatively affects health in the form of self-harm.…”
Section: Discussioncontrasting
confidence: 99%
“…4,5,9,25,36,51,54,59,60 Our findings uniquely demonstrate that, in addition to individual-level demographic and behavioral factors, the social climate of a state as measured through partisan voting practices is a strong indicator of experiencing care refusal among U.S. transgender individuals. By identifying areas where access to care barriers exist, these findings pave the way for the development of targeted public health research, programming, and intervention efforts aimed at achieving transgender health equity.…”
Section: Resultsmentioning
confidence: 58%
“…Medically affirming ones gender can include the use of exogenous hormone therapy (e.g., estrogen) or surgery (e.g., medical confirmation surgery) to feminize the body, with hormone therapy often being the first and sometimes only gender transition-related intervention sought (Coleman et al, 2012). Hormone therapy is an essential component of healthcare delivery for some transgender people, as it alleviates the psychological distress of gender dysphoria (APA, 2008, Coleman et al, 2012), and has been linked to improved mental health outcomes (e.g., reduced depression and anxiety) and quality of life (White Hughto and Reisner, 2016, Murad et al, 2010). Given that transgender women may require a variety of health services while incarcerated, access to supportive medical providers, who are knowledgeable about transgender individuals and their healthcare needs, is essential to ensuring the health of incarcerated transgender women.…”
Section: Introductionmentioning
confidence: 99%